Regional Typology and Spatial Dependent Driving Factors of Poverty in Gowa Regency, Indonesia - Ahmad Syaifullah; Andrea Emma Pravitasari; Galuh Syahbana Indraprahasta (International Journal of Economics Development Research (IJEDR), 2023)
One notable societal challenge that urban and regional development has to deal with is poverty. In this paper, we focus on rural poverty by zooming in on Gowa Regency, Indonesia. We argue the importance of considering spatial aspect in analyzing poverty. By considering this aspect, it is expected that poverty reduction programs can be tailored to the specific needs of each location. As such, the purpose of this research is to better understand the spatial dimension of rural poverty in Gowa Regency by performing three spatial analyses. This was done at first by evaluating the characteristics of each region. The next step is identifying the distribution and spatial pattern of poverty to specifically map the pattern of poverty in rural areas of Gowa Regency. Next is identifying the diverse spatial factors that influence poverty in rural areas of Gowa Regency. The analyses were performed by using cluster analysis, Spatial Autocorrelation Analysis (Global Moran Index and Local Indicators of Spatial Autocorrelation), and Geographically Weighted Regression (GWR) accordingly. The results of the study show that rural areas in Gowa Regency can be divided into several typologies. Furthermore, there is an indication that the spatial distribution of rural poverty in Gowa Regency tends to cluster. Lastly, each significant variable has different effect on rural poverty in Gowa Regency. Therefore, this study provides refined insights into possible different poverty reduction interventions for each village.